Population analysis and studies - Husain,Ishrat Z. (ed.) (Bombay, 1972)
Mukerjee was certainly the first among the Indian academicians to have foreseen the dangers of population growth to the country's economy and prosperity. His findings of the twenties in rural economy and land problems convinced him that our economic problems cannot be resolved without arresting population growth. The Census of 1931, however, disclosed an acceleration rather than a decline in t the decennial growth rate of population. This was so inspite of the Great War and the two severe epidemics during the decade. It made him face the issue directly He had already introduced population as a subject for post-graduate studies in his Department at the University. Even by mid-fifties as the UNESCO Survey of Demo graphy disclosed, it was the only Indian University where demographic research was undertaken. In 1936 he convened the First All-India Population Conference to focus national attention on the problem. For nearly a decade after that, he applied his own mind mainly to it. In quick succession came his Food Planning for Four Hundred Millions in 1938: The Regional Balance of Man in 1938: The Food Supply in 1942: The Political Economy of Population in 1944: Population Problems in South East Asia in 1944; and Roces, Lands and Food in 1946.
Keywords: Demography